Comparison of Simpler Radiation-Based ET Models with Penman Monteith model for Humid Region - Jhajharia, D; Berma, S Deb; Agrawal, G (Journal of Agricultural Engineering, 2004)
The three relatively simpler radiation-based models: Turc, Jensen-Haise and Priestley-Taylor were used to estimate reference evapotranspiration (ET0) at different humid locations of Assam, India. The Penman-Monteith model was selected as the standard for evaluating the performance of the other three radiation-based models. The averaged monthly meteorological data were used for estimating the ET0. Good correlation was found between ET0 values estimated by each of the three radiation-based models. The least and the highest values of RMSE varied between 0.16 (Gohpur) and 0.82 (Dhubri) for Priestley-Taylor model; 0.95 (Dhubri) and 1.68 (Silicorie) for Turc model; and 1.89 (Dhubri) and 2.97 (Silicorie) for lensen-Haise model. The study revealed that among all the three radiation-based models, the Priestley-Taylor model yielded average estimate of ET0 closest to the Penman-Monteith model.